An Extensive Study of the Functional Polymorphisms of Kinin-Kallikrein System in Rheumatoid Arthritis Susceptibility - Anthoula CHATZIKYRIAKIDOU,; Paraskevi V. VOULGARI,; Alexandros A. DROSOS, (Archives of Rheumatology, 2018)
Objectives: This study aims to examine the following functional polymorphisms in rheumatoid arthritis (RA) susceptibility: (i) the 587C>T of kininogen gene, (ii) the 287 bp Alu repeat insertion of angiotensin converting enzyme gene, (iii) the 9 bp insertion of bradykinin receptor 2 gene, (iv) the -58T>C of bradykinin receptor 2 gene, and (v) the -699G>C of bradykinin receptor 1 gene. Patients and methods: The study included 136 RA patients (27 males; 109 females; mean age 60.8 years; range 39 to 75 years) and 149 ethnic matching controls (30 males, 119 females; mean age 56.2 years; range 35 to 78 years). Polymerase chain reaction coupled with restriction assay was performed for 587C>T, -58T>C, and -699G>C. Results: Rheumatoid arthritis patients and controls carried the wild type allele of 587C>T; therefore, produced the high molecular weight kininogen. No significant difference was observed in genotype or allele distribution of the studied functional polymorphisms between RA patients and controls. Conclusion: Kinin-kallikrein system related genes might not be major RA susceptibility loci.